F1 and data analytics: it`s a numbers game - Tran, D. (Sports Performance & Tech, 2015)
Aside from the glitz and glamour of multi-millionaire race drivers and champagne, Formula 1 (F1) is a competitive sport consumed by data. And it is making sense of that data that which allows F1 teams to thrive.